Anomalous electrical conductivity change in MoS2 during the transition from the amorphous to crystalline phase. Issue 2 (15th January 2023) - Krbal, Milos; Prikryl, Jan; Pis, Igor; Prokop, Vit; Rodriguez Pereira, Jhonatan; Kolobov, Alexander V.
Abstract: Transition metal dichalcogenides exhibit unique properties, which make them interesting for fundamental studies and for applications in many devices. Here, we report on the anomalous electrical behavior during the amorphous-to-crystal phase transition of MoS 2 . While crystallization typically results in an increase in conductivity, the situation in MoS 2 is opposite. Amorphous MoS 2 shows a sheet resistance of 3.2 × 10 3 Ω □ with the value remaining nearly constant until 200 °C, MoS 2 samples annealed above 200 °C exhibit an unexpected two-step increase in sheet resistance. The first abrupt increase takes place after annealing at temperatures between 300 and 400 °C while the second increase occurs after heating to 700 °C with typical sheet resistance values of 1.2 × 10 5 and 8 × 10 6 Ω □ after heating to 500 °C and 900 °C, respectively. Using a combination of X-ray photoelectron spectroscopy and X-ray diffraction studies and ab-initio modeling, we argue that the large electrical conductivity observed in amorphous MoS 2 is associated with the existence of a large quantity of Mo–Mo homopolar bonds that exceed the percolation threshold. The dramatic increase in the sheet resistivity in the first step is accompanied by the formation of the Mo–S bonds upon the disassociation of homopolar Mo–Mo bonds for a further increase in the sheet resistance upon annealing temperatures of 700 °C that can be attributed to the grain boundary formation during crystallization of MoS 2 into the 2H layered structure. Graphical abstract: Highlights: Anomalous electrical conductivity change in MoS2 during crystallization. A huge change in electrical resistance suggests the use of TMDC for data storage. Three separated resistance states can be used to encode data in three logic states. The low resistance amorphous state is due to a large quantity of Mo–Mo bonds. High resistance states arise from Mo–Mo bond disruption and crystallization.